1998
DOI: 10.1007/s002590050226
|View full text |Cite
|
Sign up to set email alerts
|

Focal fluorine-18 fluorodeoxyglucose accumulation in inflammatory pancreatic disease

Abstract: Focal 2-deoxy-2[fluorine-18]fluoro-D-glucose (FDG) uptake on positron emission tomography (PET) in a pancreatic mass has been reported as a specific finding for pancreatic carcinoma. Inflammatory conditions of the pancreas and associated clinical circumstances yielding similar findings have not yet been fully defined. Among 42 patients studied by attenuation-corrected FDG PET for pancreatic disease, 12 with focal FDG uptake in the pancreas were identified as having no underlying neoplasm based on surgical find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
73
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(74 citation statements)
references
References 12 publications
1
73
0
Order By: Relevance
“…Though FDG-PET is a sensitive diagnostic modality in detecting malignant tumors, inflammation can give rise to FDG uptake in the same intensity range as pancreatic neoplasm 18 . In chronic pancreatitis, tumors detected by FDG-PET consist of degenerative necrosis surrounded by granulation tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though FDG-PET is a sensitive diagnostic modality in detecting malignant tumors, inflammation can give rise to FDG uptake in the same intensity range as pancreatic neoplasm 18 . In chronic pancreatitis, tumors detected by FDG-PET consist of degenerative necrosis surrounded by granulation tissue 29 .…”
Section: Discussionmentioning
confidence: 99%
“…However, FDG-PET cannot always differentiate between such lesions 17,18 , since the inflammatory foci of the pancreas also accumulates FDG 19,20,21,22 . In addition, previous reports have shown that patients with autoimmune pancreatitis also show intense FDG uptake 19,23,24 .…”
Section: Introductionmentioning
confidence: 99%
“…FDG is not a cancer-specific agent and is known to accumulate in cases of acute inflammation in granulomatous diseases and in autoimmune diseases [20][21][22]. Under such conditions, the suggestion is that 18 F-FDG is taken up by infiltrating cells such as macrophages, lymphocytes, and granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of 18 F-FDG in cancer tissue is thought to reflect enhanced glucose use by neoplastic cells (11)(12)(13). 18 F-FDG accumulation is observed in inflammatory lesions as well as in malignant tumors (14)(15)(16)(17). Regarding the gastrointestinal tract, 18 F-FDG PET studies have been reported in Crohn disease (18)(19)(20)(21).…”
mentioning
confidence: 99%